2019
DOI: 10.29252/ibj.23.2.142
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Nitric Oxide Induced Early Mineralization in Rat Bone Marrow Mesenchymal Stem Cells via Activation of Alkaline Phosphatase

Abstract: Background:Since the low concentration and short-time treatment with sodium nitroprusside (SNP), a nitric oxide (NO)–donor, cause no harm to rat bone marrow mesenchymal stem cells (MSCs), we studied the impact of SNP on MSCs differentiation. Methods:MSCs were treated with 100 and 1000 µM of SNP for 1 hour in every 48 hours and after 5, 10, 15, and 21 days in osteogenic media. The viability and the level of mineralization were determined using MTT assay and alizarin red staining, respectively. Morphology of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Extensively used as a venous vasodilator, sodium nitroprusside serves to immediately decrease the blood pressure in critical clinical situations [69]. The efficacy of exogenous NO on the in vitro osteogenic differentiation of mesenchymal stem cells has been the object of a recent study by Abnosi and Pari [70]. These researchers discovered that low concentrations of exogenous sodium nitroprusside (in the order of <0.1 mM generating ~1.2 nM of NO) promoted the ability to proliferate and the capacity to differentiate into osteoblasts of rat bone marrow mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Extensively used as a venous vasodilator, sodium nitroprusside serves to immediately decrease the blood pressure in critical clinical situations [69]. The efficacy of exogenous NO on the in vitro osteogenic differentiation of mesenchymal stem cells has been the object of a recent study by Abnosi and Pari [70]. These researchers discovered that low concentrations of exogenous sodium nitroprusside (in the order of <0.1 mM generating ~1.2 nM of NO) promoted the ability to proliferate and the capacity to differentiate into osteoblasts of rat bone marrow mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Felka et al reported the osteogenic inhibitory effect of exogenous NO at high concentrations (1 mM) in the early stage of osteogenesis, but in our previous study, we showed that the 100 µM of SNP as the NO-releasing agent induced the early matrix formation of BMSCs at day 5 in vitro (19,20). Some studies reported that the matrix formation starts from day 7 when the activity of ALP begins as an early gene (23,24).…”
Section: Discussionmentioning
confidence: 75%
“…SNP for 1 hour every 48 hours elevated matrix formation from day 10 of the differentiation process up to the 20th day of incubation (20).…”
mentioning
confidence: 93%
“…This suggests that the mechanism of action was independent of hydrogen peroxide formation. 163 The addition of the nitric oxide (NO) donors ( Z )-1[ N -(2-aminoethyl)- N -(2-ammonioethyl)amino]diazen-1-ium-1,2-diolate (DETA-NONOate) and sodium nitroprusside 110,169171 was also used to stimulate NO production—which belongs to reactive nitrogen species yet acts similarly to ROS. Nevertheless, while simple and convenient, due to their instability, the exogenous administration of ROS appears infeasible for tissue regeneration purposes.…”
Section: Modality Of Ros Administration and Ros-releasing Biomaterialsmentioning
confidence: 99%